Review of available approaches for ultimate bearing capacity of two-layered soils - M. Dalili Shoaei; A. Alkarni; J. Noorzaei; M. S. Jaafar; Bujang B. K. Huat (Journal of Civil Engineering and Management, 2012)
This paper presents the state of the art report on available approaches to predicting the ultimate bearing capacity of two-layered soils. The article discusses three most popular methods, including the classical method, application of the finite element method and artificial neural network. Various approaches based on these three powerful tools are studied and their methodologies are discussed.